An Analysis of the Impact of Science, Technology, Engineering, Arts, and Mathematics (STEAM) Approach on the Learning Outcomes of Islamic Education among High School Students - Nur Afif; Fatkhul Mubin (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: An Analysis of the Impact of Science, Technology, Engineering, Arts, and Mathematics (STEAM) Approach on the Learning Outcomes of Islamic Education among High School StudentsObjective: This study aims to analyze the impact of using the Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach on the learning outcomes of Islamic education (PAI) students at the Senior High School level. Methods: The research design used a survey approach. The sample was taken using a stratified random sampling technique, totaling 300 students. Data collection using questionnaires. Data analysis using analysis of variance (ANOVA). Results: The STEAM approach improves students' understanding of Islamic education materials and increases their motivation to learn. Conclusion: Applying the STEAM approach in Islamic education can improve learning outcomes and positively impact by creating a more relevant, interesting, and contextualized learning experience. Contribution: This research contributes to local governments and schools' formulation of educational policies toward the widespread use of the STEAM approach at the high school levelINDONESIAN: Analisis Dampak Pendekatan Science, Technology, Engineering, Arts, and Mathematics (STEAM) terhadap Hasil Belajar Pendidikan Agama Islam pada Siswa Sekolah Menengah AtasTujuan: Penelitian ini bertujuan untuk menganalisis dampak penggunaan pendekatan Science, Technology, Engineering, Arts, and Mathematics (STEAM) terhadap hasil belajar Pendidikan Agama Islam (PAI) siswa di tingkat Sekolah Menengah Atas. Metode: Desain penelitian menggunakan pendekatan survei. Sampel diambil menggunakan teknik stratified random sampling, berjumlah 300 siswa. Pengumpulan data menggunakan angket. Analisis data menggunakan analysis of variance (Anova). Hasil: Pendekatan STEAM meningkatkan pemahaman siswa tentang materi pendidikan Islam dan meningkatkan motivasi mereka untuk belajar. Kesimpulan: Penerapan pendekatan STEAM dalam PAI dapat meningkatkan hasil belajar dan memberikan dampak positif dengan menciptakan pengalaman pembelajaran yang lebih relevan, menarik, dan kontekstual. Kontribusi: Penelitian ini berkontribusi sebagai bahan pertimbangan bagi pemerintah daerah dan sekolah dalam merumuskan kebijakan pendidikan terhadap penggunaan pendekatan STEAM secara luas di tingkat SMA.